Start-up financing in the digital age: A systematic review and comparison of new forms of financing - Maximilian Klein; Florian Neitzert; Thomas Hartmann-Wendels; Sascha Kraus (The Journal of Entrepreneurial Finance (JEF), 2019)
Start-ups are seen as the leading force in dynamically growing economies. Limited financing opportunities often prevent entrepreneurs from realizing their innovative business ideas or taking growth opportunities. However, in the context of the technological revolution, a fundamental change in the entrepreneurial finance landscape is observed. Innovative, digital financial instruments such as Business Angel Networks, Crowdfunding, or Initial Coin Offerings provide young companies with attractive financing opportunities. Although a large number of studies focus on start-up financing in the digital age, the literature is still fragmented. By providing a systemic literature review of 85 high-quality peer-reviewed journal articles published between 1990 and 2019, we address the following purposes: First, we outline a holistic picture on the financing spectrum of start-ups in the digital age. Therefore, we classify the articles into two categories as traditional or novel financing instruments. Subsequently, we associate the different financing instruments into the various growth stages of start-ups and define them as equity or debt. Second, we evaluate the suitability of novel financing instruments based on the trade-off and pecking order theory. Third, we investigate whether new forms of financing are substitutes or complements to traditional financing forms. Furthermore, ideas for further research are suggested.
Keywords: L26; L31; G21; G23; G24; G32; 650; Entrepreneurial finance; Financing instruments; Start up financing; early stage financing; SME financ-ing; sustainable finance; systematic literature review